Morfologi Dan Mutu Fisik Benih Kenanga (Cananga odorata (Lam.) Hook.f. & Thomson forma genuina) - Arum Sekar Wulandari; Ferawati Oktia Nurhayani (Jurnal Silvikultur Tropika, 2019)
Cananga is one of the forestry plant that has high economic value and benefits. The provision of high-quality seed is necessary for establishy cananga plantation. The aim of this study was to observe the fruit morphology and analyze the physical quality of cananga seeds. This research method consisted of (1) morphological observation of seed (fruit size, number of seeds per fruit, and their correlation); (2) physical quality testing of seed (the weight of 1 000 seeds and seed moisture content). The observations showed that the fruit length were 7.40-27.5 mm, width 0.43-16.63 mm and weight 0.36-2.88 grams. The size of fruit have significant effect on the number of seeds in the fruit, there are 1-12 seeds in one cananga fruit. There are approximately 16 000 seeds in 1 kg of cananga seed. Seed moisture content of fruit that taken from tree (51.20-59.20%) is higher than seed water content of fruits that fall due to ripe physiologically (34.57-37.82%). Key words: cananga, morphological, physical quality, seed